Western Law Is More Protective, Supervision Of Children Under Guardianship: Marriage Law, KHI VS Civil Code - Simatupang, Taufik H.; Iskandar, Eka Ardianto (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to answer two problems. The first is how to regulate the supervision of child guardianship in Indonesia? Second, how effective is the implementation of supervision of children's assets under guardianship? The results of the study concluded that, First, the state's authority to supervise guardianship through BHP is not regulated in the Marriage Law and the Compilation of Islamic Law but is regulated in the Civil Code as a Western legal product. Second, the effectiveness of the BHP guardianship supervision function has not been effective. In the future, regulations are needed that accommodate Pancasila values ​​as a form of protection for children under guardianship. Therefore, it is necessary to make changes to the Marriage Law to accommodate Articles 366 and 369 of the Civil Code, as well as further research on the existence of the Compilation of Islamic Law, which is not yet known in the hierarchy of laws and regulations in Indonesia.